Analisis Perhitungan Biaya Penambangan Batu Silika Pada Departemen Tambang PT Semen Padang - Suci Rahmawati SY (Jurnal Optimasi Sistem Industri, 2011)
Cement manufacturing is consisting of four components that are limestone with the percent composition of 70%, iron sand 10%, silica 10%, and clay 10%. Source of major raw materials for cement production in PT Semen Padang are limestone and silica. The mining process is involving various costs such as direct costs, indirect costs, overhead costs, etc. Therefore, cost calculations needed to determine the selling price of produced silica. In calculating the cost of production considered various aspects, such as operating costs, material costs, labor costs. So that, it can determine cost of goods production. The research objective is calculating cost of goods manufacturing the silica. Benefit of the research for PT Semen Padang is describing cost of goods production in determining cost of goods sold. Cost of goods production that resulted for silica mining is IDR 58.000 per ton, while internal price of silica is IDR 53.851 per ton. Research result is show that there is difference between results based on Full costing method with current price. This shows that several other factors is necessary considered in calculating the cost of goods production.